Asynchronous output feedback dissipative control of Markovian jump systems with input time delay and quantized measurements. (February 2019) - Liu, Yajuan; Fang, Fang; Park, Ju H.; Kim, Haekyoung; Yi, Xiaojian
Abstract: This paper considers dynamic output-feedback control for Markovian jump systems with input mode-dependent interval time delay and quantized measurements. The transitions of the considered system and the desired output feedback controllers are considered to be asynchronous. The transition probabilities of output feedback controllers are allowed to be known, uncertain, and unknown. The main purpose of this paper is to design an asynchronous output feedback controller for Markov jump systems so that the closed-loop system is stochastically stable and achieves strict ( Q, S, R ) − α dissipativity. A sufficient condition is developed using Lyapunov functional approach. The controller gains are derived by solving a set of linear matrix inequalities. A numerical example is provided to demonstrate the effectiveness of the developed techniques.